Obesity Increases Costs with Productivity Loss Due to Disability Retirements, Independent of Physical Activity: A Cohort Study - Araujo, Monique Yndawe Castanho [UNESP]; Norberto, Maria Carolina Castanho Saes [UNESP]; Mantovani, Alessandra Madia [UNESP]; Turi-Lynch, Bruna Camilo [UNESP]; Santos, Lionai Lima Dos [UNESP]; Ricardo, Suelen Jane [UNESP]; Morais, Luana Carolina De [UNESP]; Codogno, Jamile Sanches [UNESP] (Wolters Kluwer, 2020)
Objective:Investigate whether obesity is responsible for costs due to productivity loss (PL) in adults, during 30 months of follow-up.Methods:Absenteeism and disability retirement were considered as PL. For classification of obesity, body mass index (BMI) and waist circumference (WC) values were considered. The statistical software BioEstat (release 5.0) was used and the significance level was set at P value < 0.05.Results:For the men, BMI and WC accounted for ∼60% and ∼30% of retirement due to disability (P = 0.001). For the women, this percentage represented ∼19% for BMI and ∼8% for WC, both P < 0.05. Physical activity was not a significant confounder in any of the analyses (P > 0.05).Conclusion:Total and abdominal obesity were responsible for increased costs from PL due to early retirement among adults aged 50 years or older.
Keywords: absenteeism; health care costs; obesity; physical inactivity; productivity loss